WHO Surgical Checklist and Its Practical Application in Plastic Surgery. (14th February 2011) - Abdel-Rehim, Shady; Morritt, Andrew; Perks, Graeme
Abstract : The WHO surgical checklist was introduced to most UK surgical units following the WHO "Safe Surgery Saves Lives" initiative. The aim of this audit was to review patient's safety in the delivery of surgical care and to evaluate the practical application of the new WHO surgical checklist. We conducted a retrospective audit of patients who received operative treatment under general anaesthesia at our Plastic Surgery Department, involving a total number of 90 patients. The WHO form was compared to its former equivalents. Complications or incidents occurring during or after surgery were recorded. Using the department's previous surgical checklist, "Time out" was only performed in only 30% of cases. One patient arrived at theatre reception without a completed consent form, and two clinical incidents were reported without patients suffering harm. Following introduction of current WHO surgical checklist, "Time out" was recorded in 80% of cases. In all cases, the new WHO surgical checklist was used and no incidents were reported. The WHO surgical checklist provides a structured frame work that standardizes the delivery of care across hospitals and specialized units; however, it will take some time and practice for teams to learn to use the checklist effectively and reliably.